ANALISIS KEMAMPUAN KONEKSI MATEMATIS SISWA DALAM MENYELESAIKAN MASALAH KONTEKSTUAL PADA MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL - Hamzah, Nurliya; Abdullah, Abdul Wahab; Pauweni, Khardiyawan A.Y. (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
Connections in mathematics refer to linking mathematical concepts with other sciences and their application in everyday life situations. Solving mathematical problems related to context can be used to develop and assess students' mathematical abilities in making connections. This research aims to describe how junior high school students use mathematical connection abilities in solving predetermined contextual problems. The research method used is descriptive qualitative. Data was collected through initial ability tests and mathematical connection tests and interviews. The research results show that students with high mathematical abilities tend to be able to make mathematical connections by building mathematical models, link concepts conceptually by connecting elements in SPLDV, and operate mathematical procedures correctly. However, mathematical connections are rarely made because students do not understand the solution methods. Students who have low mathematical abilities, in general, are not able to make connections according to connection indicators. So, the conclusion is that students' ability to make mathematical connections affects their ability to solve contextual mathematical problems.